KIT STEM METAMORFOSIS (JELAJAH SIKLUS HIDUP HEWAN) UNTUK MENINGKATKAN POSITIVE RELATIONSHIP SISWA INKLUSI KELAS III SD - Adriyani, Made Devi; Riastini, Putu Nanci (Jurnal Administrasi Pendidikan Indonesia, 2025)
The low level of positive interaction among inclusive students in grade III of elementary school poses a challenge for teachers in creating a conducive, collaborative learning environment. This research aims to develop a KIT STEM Metamorphosis (Animal Life Cycle Exploration) media to improve positive relationships among inclusive students in grade III of elementary school. The research model used is the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The subjects of this study were two experts in learning materials and media, two grade III teachers as practitioners, and seven grade III students. Data were collected through observation, interviews, and questionnaires, using instruments such as observation and interview guidelines, rating scale sheets, and questionnaires. The results showed that the resulting KIT STEM obtained a validity index of 1.00 according to the media content validator with very high qualifications. Teacher responses to KIT STEM reached 95% with excellent qualifications, while student responses reached 95.4% with excellent qualifications. Thus, the developed Metamorphosis STEM Kit is not only content-valid but also received very positive feedback from teachers and students. Consequently, this STEM Kit can be used as an innovative learning medium to encourage active engagement, strengthen social interactions, and support inclusive science learning in elementary schools